District population dispersion index (IDP) for estimating human resources needs at primary health care level - Álvarez, Carmela (2015)
Introduction: The Ministry of Health of Peru (MINSA) is implementing policies and strategies to ensure equitable access to care, timeliness and quality. Sufficient human resources (RHUS) properly distributed in the different levels of care is needed to accomplish this. Thus, it is essential to adequately estimate the gap of RHUS, especially at primary care level. Objectives: To develop, validate and implement a district population dispersion index (IDP) characterizing the district, and to provide dispersion in estimating RHUS gap at primary care level. Design: Observational and analytical study. Location: Directorate General Management Human Resources Development MINSA, Peru. Participants: All districts of Peru were considered for analysis. Interventions: An exploratory factor analysis was performed. It considered demographic, social and economic access to health services, obtained from the Population and Housing Censuses (2005 and 2007) and the National Continuing Survey (2006) variables. The IDP was structured and validated against the official list of villages and the perception of health officers of regional governments. Main outcome measures: IDP. Results: Out of 1 831 municipalities evaluated, we classified 1 277 districts as rural, according to the classification of the Presidency of the Council of Ministers (PCM). They were considered as scattered by the methodology. Concordance was 82%. Conclusions: The IDP is a useful indicator to estimate the gaps of RHUS for health services at primary care level in Peru.